2019
DOI: 10.3390/md17010057
|View full text |Cite
|
Sign up to set email alerts
|

Clerodane Diterpenes from the Marine Sponge Raspailia bouryesnaultae Collected in South Brazil

Abstract: The marine sponge Raspailia bouryesnaultae, collected in South Brazil, was selected for detailed investigation considering the results of a screening that pointed to an in vitro antiproliferative effect against non-small cells of human lung cancer (A549) and anti-herpes activity against Herpes Simplex virus type 1 (KOS and 29R strains) of ethanolic extracts. The fractionation and chemical investigation of the sponge’s hexanic fraction led to the isolation and structural elucidation of six clerodane diterpenes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Lhullier et al (2019) isolated six clerodane diterpenes ( 59 – 64 ) from the marine sponge Raspailia bouryesnaultae . The compounds displaying the most potent cytotoxic activity were those containing a hydroxyl group at C-6, with IC 50 values lower than 25 μM [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lhullier et al (2019) isolated six clerodane diterpenes ( 59 – 64 ) from the marine sponge Raspailia bouryesnaultae . The compounds displaying the most potent cytotoxic activity were those containing a hydroxyl group at C-6, with IC 50 values lower than 25 μM [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…Induction of G1 arrest (↑p27 and ↓cyclin D1), apoptosis (↑PARP cleavage and ↑ROS generation), and autophagy (↑LC3B II/I, ↑Atg5, and ↓p62). [ 51 ] Raspailia bouryesnaultae raspailol ( 59 ), raspadiene ( 60 ), kerlinic acid ( 61 ), kerlinic acid methyl ester ( 62 ), annonene ( 63 ), and 6-hydroxyannonene ( 64 ) Clerodane diterpenes Isolation A549 (NSCLC) 59 : 24.12 μM 60 : 100.3 μM 61 : 66.22 μM 62 : 20.63 μM 63 : 143.7 μM 64 : 24.52 μM (48 h) NR [ 54 ] Acanthodendrilla sp. (S)- acanthodendrilline ( 65 ) and (R)- acanthodendrilline ( 66 ) Bromotyrosine alkaloid Chemical synthesis H292 (NSCLC) 65 : 58.5 ± 6.7 μM 66 : 173.5 ± 24.7 μM (72 h) NR [ 55 ] Chondrosia corticata halichondramide ( 67 ), jaspisamide A ( 68 ), neohalichondramide ( 69 ), halishigamide D ( 70 ), and (19Z)-halichondramide ( 71 ) Oxazole-containing macrolide Isolation A549 (NSCLC) 67 : 0.045 μM 68 : 32.63 μM 69 : 3.73 μM 70 : 1.65 μM 71 : 0.024 μM (72 h) G2/M cell cycle arrest (↑p53, ↑GADD45α, ↓cyclin B1, ↓cyclin A, ↓CDC2, and ↓CDC25C) and suppression of the Akt/mTOR signaling pathw...…”
Section: Resultsmentioning
confidence: 99%
“…A total of six clerodane diterpenoids were isolated from marine sponge Raspailia bouryesnaultae , and their anti-herpes activity was tested against herpes simplex virus type 1 (HSV-1). All of the diterpenoids displayed potential antiviral activity with an IC 50 lower than 25 μM, especially the new compound 120 , which inhibited HSV-1 (KOS and 29R strains) replication by 83% and 74% (IC 50 = 81.39 ± 9.82 and 74.93 ± 7.30 μg/ml) respectively ( Lhullier et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…All of the diterpenoids displayed potential antiviral activity with an IC 50 lower than 25 μM, especially the new compound 120, which inhibited HSV-1 (KOS and 29R strains) replication by 83% and 74% (IC 50 = 81.39 ± 9.82 and 74.93 ± 7.30 μg/ml) respectively (Lhullier et al, 2019).…”
Section: Clerodane Diterpenoidsmentioning
confidence: 98%
“…Like gibberellins that have been isolated from both plants (He et al, 2020) and fungi (Tudzynski, 2005), clerodanes have been reported from several hundred different plant species (Li et al ., 2016; Merritt and Ley, 1992), as well as fungi (Andersen et al, 1983), bacteria (Nakano et al, 2015) and marine animals (Lhullier et al, 2019). Although clerodanes have been isolated from plants of the Asteraceae, Euphorbiaceae, Flacourtiaceae, and Menispermeaceae families, more than 50% of reported clerodanes have been isolated from members of the family Lamiaceae (Li et al ., 2016; Merritt and Ley, 1992) and these have attracted considerable attention for their biological activities (Li et al ., 2016).…”
Section: Introductionmentioning
confidence: 99%